Helicobacter pylori에 감염된 생쥐에서 위염에 대한 위산의 역할 - 김성수; Sung Soo Kim; 이여민; Yeo Min Lee; 김형근; Hyung Keun Kim; 김진일; Jin Il Kim; 채현석; Hiun Suk Chae; 정인식; In Sik Chung; et al. (The Korean journal of gastroenterology, 2007)
목적: 위산이 H. pylori 감염에 의한 위염 진행을 억제할 수 있는지 알아보고자 대상 및 방법: C57BL/6 생쥐 28마리에 H. pylori (SS1 균주)를 감염시켰다. 7마리씩 4군으로 나누어 I군은 처치 없이 관찰하고, II군은 위투여(sham injection), III군은 펜타가스트린 125μg/kg, IV군은 펜타가스트린 250μg/kg을 일주일에 3회 피하 주사하여, 7개월 후 위 점막 pH를 측정하고, 위 점막의 H. pylori 군집도, 호중구 활성도, 만성 염증, 위선 위축의 변화를 관찰하였다. 결과: H. pylori 군집도는 체부와 전정부 모두 군 간에 차이가 없었다. 호중 구 활성도는 체부에서 타군에 비해 IV군이 현저히 낮았으며(I군, 1.71; II군, 1.0; III군, 2.71; IV군, 0.29, p＜0.05), 전정 부에서는 군 간에 차이가 없었다. 만성 염증 세포의 침윤정도는 체부에서 III군에 비해 IV군이 현저히 낮았으나(1.86 vs. 1.0, p＜0.05), 전정부에서는 군 간에 차이가 없었다. 위축 정도는 군 간에 통계적인 차이가 없었다. 대상 위 점막의 평균산도 3.2를 기준으로 고위산분비군과 저위산분비군으로 나누어 비교했을 때 체부에서 고위산분비군은 저위산분비군에 비해 H. pylori 군집도(1.4 vs. 2.4; P=0.04), 호중구 활성도(0.9 vs. 2.3; p=0.018) 및 만성 염증 세포의 침윤 정도(1.2 vs. 1.8; p=0.011) 모두 유의하게 낮았다. 결론: 위산은 위내 H. pylori에 의한 위염 확산을 억제하는 데 중요한 역할을 하는 것으로 생각한다. Background/Aims: This study was designed to investigate the role of gastric acid in the extent of H. pylori-induced gastritis. Methods: Twenty eight mice were innoculated with live H. pylori. They were allocated into four groups. Mice in group I received no treatment, group II mice were treated with sham injection, group III received 125μg/kg body weight of pentagastrin, while group IV received 250μg/kg body weight of pentagastrin subcutaneously three times a week. After 7 months, the mucosal pH, H. pylori density, neutrophils and monocytes infiltration, and the degree of atrophy were assessed in the stomach. Results: In the gastric body, the densities of H. pylori were not different among groups. The degree of neutrophil infiltration was significantly lower in group IV compared to other groups (p＜0.05). The degree of monocyte infiltration was also significantly lower in group IV than group III (p＜0.05). In the gastric antrum, there was no significant difference of the H. pylori density, neutrophil and monocyte infiltration, and degree of atrophy among the groups. The mice with the gastric mucosal pH lower than mean of 3.2 had significant lower level of H. pylori density (1.4 vs. 2.4, p=0.04), and infiltration of neutrophils (0.9 vs. 2.3, p=0.018), and monocytes (1.2 vs. 1.8; p=0.011) than the those with mucosal pH above 3.2 in the body of stomach. Conclusions: Gastric acid plays a role in suppressing the proximal propagation of H. pylori-induced gastritis to the body of stomach. (Korean J Gastroenterol 2007;50:363-369)